Kadar Protein Dan Organoleptik Yoghurt Jagung Dengan Penambahan Konsentrasi Starter Dan Madu Yang Berbeda - Prastiani, Desi; , Dra. Hj. Suparti, M.Si (2015)
Yogurt is a refined product of fermented beverages. This study uses corn seed extract as the main ingredient of making yogurt. The purpose of this study was to determine the effect of the addition of starter and honey concentration on protein content, organoleptic and acceptance of yogurt corn. The high reducing sugar that contain in corn and honey is one of the main components to increase activities of lactic acid bacteria in fermentation. The method used is experiment with completely randomized design (CRD) and that two-factor factorial. The first factor is the concentration of starter (S) which comprises three levels of treatment is 3%, 5%, and 7% and the second factor is honey concentration (M) which comprises three levels of treatment that is 8%, 10%, and 12% with 3 repetitions. The results showed that there was no effect of the addition of starter concentration and honey yogurt to increase the protein content of corn, but there was an interaction between the addition of starter concentration and the protein content of yogurt honey corn. The highest protein contained in the combination treatment S1M1 (starter 3% and honey 8%) of 0.625%, while the protein content was lowest for the treatment combination S3M3 (starter 7% and 12% honey) of 0.23%. Organoleptic results showed that the addition of starter and honey concentration affect the organoleptic quality and acceptance of yogurt corn. Combination treatment to obtain the best organoleptic results are S3M2 (starter 7% and 10% honey) with characteristic brownish-yellow color, taste sour, somewhat viscous texture, pleasant aroma and acceptance like.